Key concepts in race and ethnicity - Meer, Nasar, 1980- (Los Angeles : SAGE, 2014)
'A conceptually power-packed volume that is at once erudite and accessible, expansive and focused, true to sociological traditions yet stimulatingly exploratory. Scholars and students will be served very well by this absorbing, far-reaching enquiry into ethnicity and race.' - Raymond Taras, Tulane University'[W]hat Meer offers with this distinctive new volume is a brief survey of the academic approach to key subjects in this area. For example, the entry titled'Racialisation' opens with the provenance of the subject in the works of W. E. B. Du Bois and Frantz Fanon; then Meer traces debates about whether the concept can be projected back upon history... Meer offers in-depth coverage of 28 concepts, including'Citizenship,''Hybridity,''Intersectionality,''Post-colonialism,''Transnationalism,' and more Students wanting a guide into the ...
Introduction -- Why a new book on race and ethnicity? -- Carving nature at its joints -- Identity and dispersion -- Reflexivity -- How to use this book -- Antisemitism -- Blackness -- Citizenship -- Diaspora -- Equalities and inequalities -- Ethnicity -- Euro-Islam -- Health and well-being -- Hybridity -- Integration -- Interculturalism -- Intersectionality -- Islamophobia -- Migration -- Mixedness -- Multiculturalism -- Nationalism -- Orientalism -- Political participation -- Post-colonialism -- Race -- Race relations -- Racialisation -- Recognition -- Secularism -- Super-diversity -- Transnationalism -- Whiteness.
Includes bibliographical references and index.
Text in English.
Description based on MARC record for print version.
Keywords: Ethnicity; Race; Ethnicity; Race; Ethnizita?t.; Rasse; Theorie; Etnicitet